Chloroplastic photoprotective strategies differ between bundle sheath and mesophyll cells in maize (Zea mays L.) Under drought - Liu, Wen-Juan; Liu, Hao; Chen, Yang-Er; Yin, Yan; Zhang, Zhong-Wei; Song, Jun; Chang, Li-Juan; Zhang, Fu-Li; Wang, Dong; Dai, Xiao-Hang; Wei, Chao; Xiong, Mei; et al. (Frontiers in Plant Science, 2022)
Bundle sheath cells play a crucial role in photosynthesis in C4 plants, but the structure and function of photosystem II (PSII) in these cells is still controversial. Photoprotective roles of bundle sheath chloroplasts at the occurrence of environmental stresses have not been investigated so far. Non-photochemical quenching (NPQ) of chlorophyll a fluorescence is the photoprotective mechanism that responds to a changing energy balance in chloroplasts. In the present study, we found a much higher NPQ in bundle sheath chloroplasts than in mesophyll chloroplasts under a drought stress. This change was accompanied by a more rapid dephosphorylation of light-harvesting complex II (LHCII) subunits and a greater increase in PSII subunit S (PsbS) protein abundance than in mesophyll cell chloroplasts. Histochemical staining of reactive oxygen species (ROS) suggested that the high NPQ may be one of the main reasons for the lower accumulation of ROS in bundle sheath chloroplasts. This may maintain the stable functioning of bundle sheath cells under drought condition. These results indicate that the superior capacity for dissipation of excitation energy in bundle sheath chloroplasts may be an environmental adaptation unique to C4 plants.